2018
DOI: 10.1002/jbio.201700238
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effects of maternal alcohol consumption on murine fetal brain vasculature using optical coherence tomography

Abstract: Prenatal alcohol exposure (PAE) can result in a range of anomalies including brain and behavioral dysfunctions, collectively termed fetal alcohol spectrum disorder. PAE during the 1st and 2nd trimester is common, and research in animal models has documented significant neural develop mental deficits associated with PAE during this period. However, little is known about the immediate effects of PAE on fetal brain vasculature. In this study, we used in utero speckle variance optical coherence tomography, a high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 56 publications
1
29
0
Order By: Relevance
“…To the best of our knowledge, this is the first proteomic study in the FASD field to identify changes in the fetal hippocampus, cortex, and cerebellum following gestational alcohol exposure. We herein demonstrate that chronic binge alcohol exposure has specific and substantial effects on fetal brain regions highly vulnerable to the teratogenic effects of gestational alcohol exposure, particularly in the hippocampal region, in alignment with prior studies utilizing comparable rodent models of gestational alcohol exposure (3941). Previous rat models of gestational alcohol exposure have implicated hippocampal deficits which manifested as altered synaptic plasticity (42) and functional connectivity (39) and was evidenced through impaired behavioral tasks in memory, learning, and spatial navigation.…”
Section: Discussionsupporting
confidence: 82%
“…To the best of our knowledge, this is the first proteomic study in the FASD field to identify changes in the fetal hippocampus, cortex, and cerebellum following gestational alcohol exposure. We herein demonstrate that chronic binge alcohol exposure has specific and substantial effects on fetal brain regions highly vulnerable to the teratogenic effects of gestational alcohol exposure, particularly in the hippocampal region, in alignment with prior studies utilizing comparable rodent models of gestational alcohol exposure (3941). Previous rat models of gestational alcohol exposure have implicated hippocampal deficits which manifested as altered synaptic plasticity (42) and functional connectivity (39) and was evidenced through impaired behavioral tasks in memory, learning, and spatial navigation.…”
Section: Discussionsupporting
confidence: 82%
“…39 Angiographic OCT is a functional extension of OCT that was developed to image microvasculature. [40][41][42][43][44][45][46] We have utilized angiographic OCT to assess the effects of prenatal exposure to one dose of ethanol, 47 a synthetic cannabinoid, 48 and nicotine on the fetal brain. 49 This study uses correlation mapping optical coherence angiography (cm-OCA) 50 to assess dose-dependent fetal brain vasculature changes due to maternal exposure to ethanol in a mouse model in utero.…”
Section: Introductionmentioning
confidence: 99%
“…We followed a similar protocol to Gilbert et al . However, in our work, the SCB was dissolved in DMSO instead of ethanol because our previous work has shown that ethanol causes significant acute fetal brain vasoconstriction . It can be seen from Figure that there is a slight increase in vasculature in the sham group.…”
Section: Discussionmentioning
confidence: 97%
“…Pregnant mice were intraperitoneally exposed to CP‐55940, a well characterized compound in SCB research, and cm‐OCA was used to visualize the fetal brain vasculature every 5 minutes for 45 minutes post‐exposure. Our results show a drastic decrease in fetal brain vasculature as compared to the sham group, similar to results obtained when pregnant mice were administered a binge‐like bolus of ethanol .…”
Section: Introductionmentioning
confidence: 99%